MINAT BELI PENGGUNA ASURANSI AXA MANDIRI YOGYAKARTA DIPENGARUHI OLEH HARGA DAN KUALITAS PRODUK - Anggapratama, Reza; Irnawati, Dwi; Kustaji, Kustaji; Rizqi Agustino, Muhammad; Noor, Fauzian; Fadila, Esti Nur; Niswah, Syifa’un; Selviana, Sova (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
This exploration aims to see if cost and item quality impact buying interest in AXA Mandiri Yogyakarta. Various Straight Relapse is the examination approach. This examination shows how cost and item quality impact shoppers' longing to purchase AXA Mandiri Yogyakarta. For this examination, non-likelihood inspecting was utilized. To gather information, every respondent was given a poll of 100 individuals. The examination system uses various direct relapses. Research discoveries show that factors that impact cost and, by and large, item quality impact purchasers' purchasing propensities, with a determined F of 25.536 F table of 3.09. The discoveries additionally show that cost impacts buying choices when the count is 6.030 ttable 1.988. The item quality variable impacts buy expectations with a count of 2.504, more prominent than the ttable of 1.984. In light of the coefficient of assurance definition test (adjusted R2), the cost and item quality factors contribute 33.4% to the variety of buying interest factors. Interestingly, factors other than this exploration added to an abundance of 66.6%. The cost and nature of products can impact customers' longings to purchase AXA Mandiri Yogyakarta. AXA Mandiri Yogyakarta, the board guarantees that the objective market finds the item quality alluring and cost stable.